A Downside to the Entrepreneurial Personality?. (22nd August 2014) - Miller, Danny
<x xml:space="preserve">Abstract</x> The literature on entrepreneurship bears a distinctly positive cast, often with good reason. Entrepreneurs and their innovations have contributed enormously to national wealth, and so scholars have examined the personalities, capabilities, and contexts underlying these contributions. However, despite some early work, the negative aspects of the entrepreneurial personality have been largely ignored. We shall argue that given the nature of the challenges facing many entrepreneurs and the consequent demands of their jobs, certain personality traits will be quite valuable to them. These, however, tend to be Janus‐faced in that positive attributes, such as energy, self‐confidence, need for achievement, and independence, may sometimes devolve naturally into aggressiveness, narcissism, ruthlessness, and irresponsibility. Given the costly repercussions of the latter characteristics, we urge more study of their nature and causes among entrepreneurs.